2021
DOI: 10.3390/ani11082375
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Niche of Syntopic Granivores in Commercial Orchards and Meadows

Abstract: In agricultural habitats, diets and trophic positions of syntopic granivorous small mammals are not known sufficiently. Agroecosystems may be quite complex isotopically and the most complex situation concerns the nitrogen-15 isotope as δ15N values are influenced by many internal and external fluxes. We analysed the isotopic niches of striped field (Apodemus agrarius), yellow-necked (Apodemus flavicollis), and harvest (Micromys minutus) mice living sympatrically and syntopically in apple and plum orchards, rasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We, therefore, compared the central positions of the stable isotope ratios in the hair of syntopic small mammals in the commensal habitats with data on the same species from other disturbed habitats in Lithuania, namely commercial orchards and berry fields [48,49], flooded meadows [50] and flooded forest (Balčiauskas et al unpublished). In two species, A. flavicollis and C. glareolus, a comparison was also possible with the environment of a cormorant colony in Juodkrant ė, which was characterized by the ultimate level of disturbance in the form of biological pollution [39].…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, compared the central positions of the stable isotope ratios in the hair of syntopic small mammals in the commensal habitats with data on the same species from other disturbed habitats in Lithuania, namely commercial orchards and berry fields [48,49], flooded meadows [50] and flooded forest (Balčiauskas et al unpublished). In two species, A. flavicollis and C. glareolus, a comparison was also possible with the environment of a cormorant colony in Juodkrant ė, which was characterized by the ultimate level of disturbance in the form of biological pollution [39].…”
Section: Discussionmentioning
confidence: 99%
“…in which authors found no gender differences in the concentration of various chemical elements in muscle and bone samples [ 80 ]. Likewise, no differences in isotopic values depending on age, sex or breeding condition have been found in several rodent species, including the wood mouse [ 51 , 70 , 74 , 75 , 81 , 82 , 83 , 84 ]. Overall, the non-variation in elemental and isotopic values due to individual traits could be attributed to the observed lack of individual differences in food intake inside traps.…”
Section: Discussionmentioning
confidence: 99%
“…We show that commercial orchards are suitable habitats for various granivore and herbivore species and may support high abundances. As a source of provided foods, represented by the trophic niches of species, orchards are different from "wild" or "natural" habitats in as much as they are scarce in seeds for granivores [43], this thus influencing competition for food in herbivores [44]. Habitat characteristics have only so far been analyzed in general in terms of age and crop type ( [39] and this paper), though it is also possible that the structural diversity of vegetation may have an influence on diversity of small mammals in orchards and surrounding areas [53,68].…”
Section: Discussionmentioning
confidence: 99%